The Effect of Climate Change on the Probability of Conservation: Fisheries Regulation as a Policy Contest - Urs Steiner Brandt (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2006)
This paper considers the policy outcome of a contest between two opposing in-terest groups: the incumbent fishermen and a group of conservationalists. The objective of the fishermen is to maximize profit, and they are (partly) concerned over future profitability as well, while the conservationalists have the aim of re-ducing current fishing effort in order to protect fish resources. The probability of a result of overfishing is dependent on the relative benefits the two groups receive if their preferred policy wins the contest. This model enables us to pre-dict how climate change induces changes in the underlying bionomic model and affects the probability of conservation. The main result is that the likelihood of conservation increases when climate change implies a larger percentage in-crease in the conservation value to the conservationalists than the percentage increase in the commercial value for the fishermen.
Keywords: Q22; D72; L5; 330; Political contest; probability of conservation; fisheries management; climate change; Fischereipolitik; Fischschutz; Klimawandel; Interessenpolitik; Spieltheorie; Theorie